POLITIK HUKUM DAN HAM ( Kajian Hukum Terhadap Kewajiban Pemenuhan dan Perlindungan Hak Asasi Manusia Dalam Konstitusi Indonesia ) - Zaini, Naya Amin (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2016)
The 1945 Constitution explain that Indonesia is a country based on law, that law as the main parameter in making policy and directing ideal of the country . Policy and orientation of country is inseparable from an Indonesian nation ideology and Indonesian basic norms. Because nation ideology is an characteristic of Indonesian nation in inspiring the material substance of constitution and legislation. In recognizing fundamentally ideology values of Indonesian nation can be traced in the thinking of the founders of Indonesian nation. The founders of Indonesian nation has initiated a debate, design, structure, crystallization great ideas to directing the ark of Indonesian toward a law nation-country that modern, large and create a better fate. Debate and formulation of basic values integrated in constitution and legislation is related to format of citizens' basic values that must be respected, protected and fulfilled by the Republic of Indonesia named human rights (HAM).